A STUDY ON THE APPLICABILITY OF TRAPEZOIDAL FUZZY AHP WITH FEATURE SELECTION: THE CASE OF SKSS SCHOLARSHIP RECIPIENTS AT BAZNAS EAST JAVA - Syamil Waris Dien Muhammad; Abdulloh Hamid; Hani Khaulasari; Dian Candra Rini Novitasari; Moh Hafiyusholeh (PATTIMURA UNIVERSITY, 2026)
The One Family One Graduate (SKSS) scholarship program, managed by BAZNAS East Java, aims to alleviate the financial burden of higher education for underprivileged communities. However, the absence of clearly defined weights for each selection criterion may lead to unfairness in the selection process. This study aims to determine the objective weights of each criterion and to rank prospective scholarship recipients using the Trapezoidal Fuzzy AHP approach. The data were obtained from 78 scholarship applicants for the 2024 SKSS period and from questionnaires completed by three expert respondents (expert judgment). Feature selection was conducted to identify the most relevant criteria, resulting in 13 selected variables are tuition fee per semester (K₁), father's latest education level (K₂), father's income (K₃), mother's latest education level (K₄), mother's income (K₅), house size (K₆), amount of family installments (K₇), number of parental dependents (K₈), income of working family members (K₉), type of transportation used to campus (K₁₀), distance from home to campus (K₁₁), monthly allowance (K₁₂), and monthly income if the student is working (K₁₃). The results show that the criterion with the highest weight is tuition fee per semester (0.139142), while the lowest is Type of transportation to campus (0.059970). The highest priority subject is Subject 74 (S_74) with a total weight of 0.7964, whereas Subject 23 (S_23) ranks lowest with a total weight of 0.7723. These findings are expected to enhance the objectivity and fairness of the SKSS scholarship selection process.